EFFECT OF NPL AND LDR ON ROA of PT. BANK RAKYAT INDONESIA. TBK WITH CAR AS AN INTERVENING VARIABLE - Supeni, Nely (Universitas Muhammadiyah Jember, 2019)
This study is to determine the effect of NPL and LDR on the ROA of PT. Bank Rakyat Indonesia Tbk With CAR As an Intervening Variable. The method of data collection in this study is by collecting data from the financial statements of PT. Bank Rakyat Indonesia TbK from the period 2013 to 2017. Analysis of the data that is suitable for use in this study is path analysis (path analysis). The result of the analysis that has been done is that NPL has no significant effect on CAR because the significance level is 0.114, which means 0.114> α. LDR has no significant effect on CAR because the significance level is 0.717 which means> α. NPL does not significantly influence ROA because the significance level is -0.790 which means 0.790> α. LDR does not significantly affect ROA because the significance level is 0.386 which means> α. CAR does not significantly influence ROA because the significance level is 0.225 which means> α. CAR is able to mediate between the NPL variable and the ROA variable because the value of the Indirect NPL Effect on ROA through CAR is 1.069 X -1.045 = -1.117105, which means 1.117105> 0.159. CAR is not able to mediate between the LDR variable and the ROA variable because the value of the Indirect LDR Effect on ROA through CAR is -0.165 X -1.045 = 0.172425 which means 0.172425 <0.324.